2017
DOI: 10.1097/brs.0000000000001989
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low-Load Motor Control Exercises and a High-Load Lifting Exercise on Lumbar Multifidus Thickness

Abstract: Study DesignRandomized controlled trial ObjectiveThe aim of this study was to compare the effects of low-load motor control exercises and a high-load lifting exercise, on lumbar multifidus (LM) thickness on either side of the spine and whether the effects are affected by pain intensity or change in pain intensity, among patients with nociceptive mechanical LBP. Summary of Background DataThere is evidence that patients with low back pain may have a decreased size of the (LM) muscles with an asymmetry between si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(65 citation statements)
references
References 36 publications
0
64
0
1
Order By: Relevance
“…Contrastingly, Chung et al [61] showed that motor control exercise increased lumbar multifidus size, although Chung et al [61] only used a per-protocol analysis, which may overestimate the magnitude of change [62]. Berglund et al [63] provided evidence that exercise may increase multifidus size, but was not conclusive regarding which type of exercise may be more beneficial. Generally, loads of 40-80%1-RM are recommended to maximize muscular hypertrophy [48].…”
Section: Paraspinal Muscle Sizementioning
confidence: 99%
“…Contrastingly, Chung et al [61] showed that motor control exercise increased lumbar multifidus size, although Chung et al [61] only used a per-protocol analysis, which may overestimate the magnitude of change [62]. Berglund et al [63] provided evidence that exercise may increase multifidus size, but was not conclusive regarding which type of exercise may be more beneficial. Generally, loads of 40-80%1-RM are recommended to maximize muscular hypertrophy [48].…”
Section: Paraspinal Muscle Sizementioning
confidence: 99%
“…12 Diminished lumbar musculature size and integrity and core abdominal and low back muscle-weakening are associated with spinal issues and can result in motor control deficiencies and asymmetries. [13][14][15][16][17][18][19][20] Biomechanical research suggests that individuals with recurrent spine issues lack adequate spinal stabilizing contractions and may demonstrate impaired postural control, delayed muscle reflex latencies, and trunk muscle recruitment pattern abnormalities. 21,22 which is why physical fitness and precise, consistent swing mechanics have become such an integral part of a professional golfers preparation for the sport.…”
Section: A Sport Of Athletes With a New Approachmentioning
confidence: 99%
“…This paper builds the model of “Motor-Load” to study the effect of the stiffness coefficient of the torsion bar on the body height adjustment. 18…”
Section: Analysis Of Three Core Functions Of Iteasmentioning
confidence: 99%